THE HIGH DIETARY FIBER, IRON AND ZINC PUDDING MADE FROM KELOR FLOUR ENRICHE WITH GINGER AS A GOOD SOURCE OF NUTRITION FOR PREGNANT WOMEN - Ai Kustiani; Atikah Adyas; Samsu Udayana Nurdin; Yaktiworo Indriani (Proceeding B-ICON, 2022)
The results of the Indonesian Nutritional Status Study in 2021 show that the prevalence of stunted in children is quite high it is 24.4%. Therefore, various strategies are needed to achieve the target, one of which is the fulfillment of nutrition for pregnant women as a preventive aspect of stunted. Kelor is one of the vegetables with high nutrients contents and can protect against oxidative stress also have potential as a ligand for stunting prevention through its antioxidant activity. Adding kelor leaves flour to the crackers made with catfish flour can increase protein and minerals but has a lack of an unpleasant aroma and the product is only limited to crackers. This research purposed to develop the product from kelor that is pudding from kelor and ginger as a food source of dietary fiber and minerals for pregnant women. The best formula chosen from organoleptic was is pudding with the addition 1.4% ginger and 100 g kelor leaves flour. The pudding contain 4.4% dietary fiber, 44.42 mg/100g iron, and 6.94 mg/100g zinc respectively. Selected pudding contain more than 6 g/100 g dietary fiber and more than 30% of iron and zinc standart for pregnant women group based on nutrition label reference (ALG, for Indonesian), so it can be claimed as a high dietary fiber, iron and zinc food.